Hubungan Emisi Karbon Dioksida dan Produk Domistik Bruto di Indonesia Periode 2000-2019 (Kajian Elastisitas dan Shift Share) - Indah Nurhidayati; Agustono Agustono (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2024)
Economic development has positive and negative impacts on society. One of the negative impacts that occurs is the emergence of greenhouse gases (GHGs). GHG is a gas that causes climate change, disrupting the sustainability of economic development. On the other hand, economic growth also has a positive impact in the form of benefits in the form of goods and services produced. Looking at these facts, the expected economic development can increase GDP and reduce carbon dioxide emissions (CO2e). Based on this, this research aims to (1) find out the effect of GDP on CO2e emissions, (2) find out changes in the elasticity of GDP on CO2e emissions for the 2000-2009 and 2010-2019 periods, and (3) find out which sectors can reduce CO2e emissions and who is the trigger for changes in CO 2 e emissions. The data used in the research is secondary data from 2000-2019 from BPS Indonesia. The study was conducted in 2023. Sample for 20 years. The analysis used is regression combined with an intercept dummy, elasticity dummy, and shift share. CO2 emissions match GDP values, approximate benefits, and GHGs. The research results show that GDP positively affects CO2e emissions with an elasticity value greater than 1. The results of the shift-share analysis show that policies at the national level still make a positive contribution to CO2e emissions. Sectoral policies provide varying results. The suggestion that can be given is that GDP is still increasing CO2e emissions. Steps that can be taken by all economic actors, such as the government, entrepreneurs, and society, must prioritize actions that mitigate GHG by seeking to increase GDP and reduce CO2e emissions, namely by combining policy efficiency and sustainability.